Effect of sintering temperature on microstructure and mechanical properties of Ti(C,N)-HfN/Ti(C,N)-WC laminated ceramics - GAO Jiaojiao; PING Ping; HU Shiheng; SONG Jinpeng (Fenmo yejin jishu)
Ti(C,N)-HfN/Ti(C,N)-WC laminated ceramics were prepared by alternately making layer method and vacuum hot pressing sintering technology, using Ti(C,N) as the matrix phase, HfN and WC as the reinforced phases for the different layers, and metal Ni and Mo as the binder phases. The effects of sintering temperature on the microstructure and mechanical properties of the laminated ceramics were investigated. The results show that with the increase of sintering temperature, the grains grow up gradually. When the sintering temperature is 1350 ℃ and 1400 ℃, the grains are small but unevenly distributed with many micro-defects. At the sintering temperature of 1450 ℃ and 1500 ℃, the grains are uniform (~1 μm) and there are fewer micro-defects. However, when the sintering temperature reaches 1550 ℃, a large number of coarse grains (~2 μm) appear. Moreover, with the increase of the sintering temperature, the flexural strength, Vickers hardness, and fracture toughness of the laminated ceramics increase first and then decrease. The laminated ceramic sintered at 1450 ℃ shows the better comprehensive mechanical properties, the flexural strength, Vickers hardness, and fracture toughness are (1263.6±17.1) MPa, (18.5±0.3) GPa, and (8.2±0.1) MPa·m1/2, respectively. In addition, the Ti(C,N)-HfN/Ti(C,N)-WC laminated ceramics exhibit the co-existence model of intergranular fracture and transgranular fracture.